KONSEP DAN PRAKTIK MANAJEMEN PADA MASA KHULAFAUR RASYIDIN - Mustafa, Desyana; Suraijiah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study examines the concepts and practices of management during the Khulafaurrasyidin period, analyzing how managerial principles were implemented by the caliphs and their relevance to modern management. The findings reveal that the Khulafaur Rasyidin consistently applied Islamic management principles rooted in trust, justice, consultation (syura), professionalism (itqan), and accountability (mas'uliyah). Abu Bakar ash-Shiddiq demonstrated firmness in crisis management and fundamental consolidation, such as the collection of the Quran. Umar bin Khattab introduced innovations in the oversight system (Muhtasib) and decentralization of government, while focusing on the welfare of the people. Uthman bin Affan emphasized integrity and social cohesion through the standardization of the Quran and a focus on professionalism. Meanwhile, Ali bin Abi Talib prioritized wisdom, dialogue, and consultation in resolving internal conflicts. Thus, the exemplary leadership of the Khulafaur Rasyidin made a tangible contribution to the development of contemporary management theory and practice, offering inspiration for ethical and adaptive leadership in various sectors of modern organizations. Penelitian ini mengkaji konsep dan praktik manajemen pada masa Khulafaurrasyidin, menganalisis bagaimana prinsip-prinsip manajerial diimplementasikan oleh para khalifah dan relevansinya bagi manajemen modern. Hasil penelitian menunjukkan bahwa Khulafaurrasyidin secara konsisten menerapkan prinsip-prinsip manajemen Islami yang berlandaskan amanah, keadilan, musyawarah (syura), profesionalisme (itqan), dan tanggung jawab (mas'uliyah). Abu Bakar ash-Shiddiq menunjukkan ketegasan dalam manajemen krisis dan konsolidasi fundamental seperti pengumpulan Al-Qur'an. Umar bin Khattab memperkenalkan inovasi sistem pengawasan (Muhtasib) dan desentralisasi pemerintahan, seraya fokus pada kesejahteraan rakyat. Utsman bin Affan berorientasi pada integritas dan kohesi sosial melalui standarisasi mushaf Al-Qur'an dan penekanan profesionalisme. Sementara itu, Ali bin Abi Talib mengedepankan kebijaksanaan, dialog, dan musyawarah dalam penanganan konflik internal. Dengan demikian, keteladanan Khulafaurrasyidin memberikan kontribusi nyata dalam pengembangan teori dan praktik manajemen kontemporer, menawarkan inspirasi kepemimpinan yang berakhlak dan adaptif di berbagai sektor organisasi modern.